Dynamics of International Business : Asia-Pacific Business Cases - Ramburuth, Prem.; Stringer, Christine; Serapio, Manuel (Cambridge ; Port Melbourne, Vic. : Cambridge University Press, 2013)
Dynamics of International Business: Asia-Pacific Business Cases brings the challenges and complexities of the contemporary international business environment into the classroom. These authentic case studies, based on recent research and events, enable students to engage with the economic, social, political and intercultural factors that impact on international business and understand how these factors are addressed in the real world.
Part IV: Operating in International Markets -- 19 Learning from experience: Purchasing industrial machinery from China / Sergio Biggemann and Andre M Everett -- 20 Country of origin labelling and the New Zealand seafood industry / Glenn Simmons, Christina Stringer and Eugene Rees -- 21 Ubisoft: Competing in the global video gaming industry / Eliseo A Aurellado -- 22 Taobao vs eBay: The fight between a local nobody and a global giant / Zhu Hang, Chai Wenjing, Su Xing and Wu Ziwei -- 23 The internationalisational of COSCO and its investment in New Zealand / Yan Shi, Christina Stringer and Gloria Lan Ge -- 24 Developing education exchanges between China and the West: The case of Bricknowledge and Mericia / William X Wei, Kimberley Howard and Evan Goodwin.
Prem Ramburuth is affiliated with University of New South Wales, Sydney.
Christine Stringer is affiliated with University of Auckland.
Manuel Serapio is affiliated with University of Colorado, Denver.
Record machine-generated from publisher information.
Keywords: International business enterprises; Entreprises multinationales; International business; International business enterprises